EC Consumer Law Compendium The Consumer Acquis and its transposition in the Member States - Schulte-Nölke, Hans 1963- (sellier european law publishers, 2008)
The EC Consumer Law Compendium presents the results of a wide-ranging study prepared for the European Commisison. This Compendium provides the reader with the necessary information for conducting pan-European cross-border consumer transactions. For the first time, the transposition of 8 key consumer directives (including those on sales, unfair terms, distance and doorstep selling as well as package travel and timeshare) into the national laws of all Member States is analyzed. The findings of this study reveal the substantial differences between the various national implementing measures as a result of utilising minimum harmonisation clauses and regulatory options
Description based on publisher supplied metadata and other sources
Keywords: Europäische Union; Recht; Consumer protection -- Law and legislation -- Economic aspects -- European Union countries; Consumer protection -- Law and legislation; Consumer protection; Mitgliedsstaaten; Verbraucherschutz; Transformation; Europäische Union. Mitgliedsstaaten